Anti-lipid-oxidation effects and edible safety evaluation of the oil extracted by a supercritical CO2 process from coix seed fermented by Monascus purpureus - Haiying Zeng; Anran Zhu; Shengling He; Mingjun Wu; Muhammad Mazhar; Anyan Wen; Na Liu; Likang Qin; Song Miao (Food Science and Human Wellness)
The physicochemical properties and composition of coix seed oil produced by Monascus purpureus fermentation and supercritical CO2 extraction were determined. Anti-lipid-oxidation and edible safety were evaluated using a cholesterol-fish oil model, acute oral toxicity assay, and genetic toxicity assay in vitro and in vivo, respectively. The results show that the extraction oil from fermented coix seed (FCS-O) had good physicochemical quality and abundant active components with physiological function. In particular, γ-tocotrienol, γ-oryzanol, coixenolide and oleic acid concentrations reached 72.83 µg/g, 745.96 µg/g, 9.65mg/g and 316.58 mg/100 g DW, respectively. The FCS-O exhibited higher antioxidant capability in inhibiting lipid oxidation and peroxidation. Compared to the blank control, the concentrations of 7-ketocholestreol and peroxide only were 8.42 µg/mL and 16.16 mmol/kg at 168 h of oxidation (P < 0.01). In addition, the FCS-O has been confirmed to be a very safe edible oil, with no acute toxicity (LD50 > 10 g/kg bw, considered actually non-toxic) and no induced mutagenicity, cytotoxicity or genotoxicity. These results serve as a good safety reference for future application of the oil from fermented coix seed. The development and utilization of this kind of oil will be beneficial as a food, food ingredient, nutritional supplement, or natural food antioxidant to promote good health function.